Fabrication and applied investigation of a muscle‐like linear actuator using lonic polymer metal composites. Issue 1 (29th May 2015) - Zhao, Gang; Sun, Zhuangzhi; Qiao, Dongpan; Yang, Junjie; Rachanne Chatto, Ashleigh; Wang, Haojun
Abstract : Focusing on the existing issues of ionic polymer metal composites (IPMC), for example, little force output and swing motion, and the applied requirements in the biomimetic artificial muscles using as the actuators, under the current framework, a muscle‐like linear actuator based on the combination of Bi‐IPMC linear actuator unit, whose experimental characteristics have been discussed in our previous work, was fabricated. The performance investigation showed that it can generate a linear movement type like artificial muscle, and there is an prominent improvement of force output capabilities compared with Bi‐IPMC linear actuator unit. Also, based on the 3D printing technique, a bionic jumping robot was experimented using the fabricating muscle‐like linear actuator, and the experimental result was validated against the feasibility of muscle‐like linear actuator. POLYM. COMPOS., 38:147–156, 2017. © 2015 Society of Plastics Engineers